2017
DOI: 10.5004/dwt.2017.20984
|View full text |Cite
|
Sign up to set email alerts
|

Combining adsorption on activated carbon with electrocoagulation process for copper removal from used water

Abstract: a b s t r a c tIn this work, electrocoagulation (EC) combined to adsorption onto granular activated carbon (GAC) was studied for the removal of copper ions. EC process was firstly optimized. The effect of the main parameters such as: pH (4-8), electrolysis time t EC (5-60 min), current density j (0.277-1.388 mAcm -2 ), conductivity, inter-electrode distanced ie (0.5-2 cm), area volume ratio S/V (3.6-14.4 m , stirring speed = 300 rpm and monopolaire connection) 97% copper removal was achieved with an energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Electrochemical technology contributes in many ways to a cleaner environment and covers a very broad range of technology [10][11][12]. Electrocoagulation process is one of the electrochemical methods that have been developed for drinking water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical technology contributes in many ways to a cleaner environment and covers a very broad range of technology [10][11][12]. Electrocoagulation process is one of the electrochemical methods that have been developed for drinking water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, comparing the quality of the effluent obtained with reuse standards and literature data, we observed that the electrocoagulation process conjugated to fixed bed adsorption of activated carbon is an effective treatment method for the post-treatment of wastewater for various reuse purposes. Table 5 Summarized guidelines for water reuse from EPA [37] Parameter More restrictive class Less restrictive class pH 6,5-8,5 10,11,12 6-9 1,2,3,4,5,6,7,8,9 BOD (mg/L) ≤ 10 1,3,5 ≤ 30 2,4,6,7,8,9 Turbidity (NTU) ≤ 2 1,3,5,10,11,12 NA 2,4,6,7,8,9 Total Col. (MPN/100 mL) ND 1,3,5,10,11,12 < 200 2,4,6,7,8,9 TSS (mg/L) < 30 2,4,7,8,9 NA 1,3,5,6,10,11,12 TOC (mg/L) < 2 10,11,12 NA 1,2,3,4,5,…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural reuse in food crops 4 Agricultural reuse in processed food crops or non-food crops 5 Unrestricted impoundments 6 Restricted impoundments 7 Environmental reuse 8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations